Aspects of IFP for citrus production in Brazil - Donadio, Luiz Carlos [UNESP] (My University, 2000)
Brazilian citriculture represents about 25% of the total world citrus production with an area of 851,518 ha and a total production of more than 17 million tons in 1996. Besides its importance to the brazilian economy, represented by more than 1 billion US $ by year from FCOJ exportation, the citriculture has problems related to low productivity, due to several cultural practices and management. The productivity would be improved by an IFP system. The main problems are related to soil, as poor conservation, use of poor drained soils and bad preparation for planting; diseases-canker, CVC, leprosis, Phytophtora gummosis and other fungus diseases; pests - mites, scales, nematodes and others; the use of disease free and improved scion and rootstocks propagative material is usual; cultural practices - as nutrition, irrigation, wind breaks, weed control, pruning, replant and others, as density planting could be improved. Some possible solutions will be discussed for improving the brazilian citrus productivity and quality by IFP, based on research made.